Aplicación de la “Niif 1: adopción por primera vez de las normas internacionales de información financiera”, en la empresa Aprenda a Manejar S.A. “Apremansa", de la ciudad de Cuenca, al período de junio a diciembre del 2011 - Yanes Izurieta, María Fernanda (2014)
The APREMANSA Company approved the adoption of International Financial Reporting Standards (IFRS), in order to receive a uniform and stable regulatory framework, given that most of the Countries of the World have implemented IFRS for purposes of preparing the financial Statements, turn its adoption will allow the presentation of financial information is reliable, objective, relevant and comparative at National and International Level. This process of conceptual research allowed to fulfill the objectives outlined in the thesis; ie Specific Plan Accounts for the company and the implementation schedule was developed, according to the Instructional Superintendent of Companies, carrying four stage analysis provided in Section 35, paragraph 7 of the IFRS for SMEs. Based on this analysis settings for the final presentation of the four financial statements currently required, together with the Accounting Policies and Explanatory Notes thereto were made, concluding the implementation process. After the conversion to IFRS NEC, the company APREMANSA managed to obtain reliable, transparent and comparable information in financial statements to all users, achieving compliance with the provisions of the Companies Super Quartermaster of schedule and tools for implementation Which will have to be made known to the involved areas due to the large impact that generated inside and outside the company.